Analyzing the Effects of Three Dimensional (3D) Stereoscopic Videogames on the Brain signals - Osman, Duaa Mohamed Amin (IRC, 2011)
Nowadays, a lot of scientists are concerned about the new technologies such as internet, video games, etc and how these technologies have impacts on the brain activities. Video games have increased in popularity between the children and the young people which emerged the significance to study the effects and the behavior of brain activities during game playing. This project carried out a research for analyzing the effects of competitive video games on the brain signals, which are displayed in three dimensional stereoscopic TVs. Since many issues arise from the impacts of the 3D stereoscopic technology on the body such as emotional sicknesses, further study will be conducted on this research to find the subjective reasons of these issues. There are two main stages in this project: the first one is data acquisition using EEG machine that are utilized for recording the brain signals while the subjects are playing 2D & 3D stereoscopic videogames. We recruited thirty healthy subjects, and then conducted experiments on them for three hours using 19 electrodes EEG cap, which was placed on the head of the participants to measure the brain signals. The second stage was analyzing and post processing for the collected data to come up with conclusion. We found the 3D technologies (3D stereoscopic active and passive) has a higher absolute power values in certain bands such as Theta, Alpha and Beta which are considered as brain waves, also the speed of information sharing and the connectivity between the brain regions (especially the relation between the visualization center and other regions of the brain) are significantly greater in the 3D technologies compared to 2D games. Moreover, we concluded the 3D stereoscopic passive has greater impacts than the 3D stereoscopic active on the brain signals.